Can open access repositories and peer-reviewed journals coexist? - Pinfield, Stephen (United Kingdom Serials Group, 2007)
It is often assumed that open access repositories and peer-reviewed journals are in competition with each other and therefore will in the long term be unable to coexist. This paper takes a critical look at that assumption. It draws on the available evidence of actual practice which indicates that coexistence is possible at least in the medium term. It discusses possible future models of publication and dissemination which include open access, repositories, peer review and journals. The paper suggests that repositories and journals may coexist in the long term but that both may have to undergo significant changes. Important areas where changes need to occur include: widespread deployment of repository infrastructure, development of version identification standards, development of value-added features, new business models, new approaches to quality control and adoption of digital preservation as a repository function.